The devil may dance [compact disc, unabridged] : a novel - Tapper, Jake (Charlie and Margaret Marder, 2021)
Charlie and Margaret Marder, political stars in 1960s Washington, DC, long for a rest, but Attorney General Robert Kennedy asks them to look into a threat to the presidency, and the security of the nation.